Peranan Jamur Rhizoctonia sp. Asal Taman Nasional Rawa Aopa Watumohai Sulawesi Tenggara terhadap Keberhasilan Aklimatisasi dan Laju Pertumbuhan Planlet Anggrek Macan (Grammatophyllum scriptum BL.) - Rita Ningsih; Sri Ambardini; Denofia Denofia (Al-Kauniyah: Jurnal Biologi, 2014)
The aim of this research was to know the role of Rhizoctonia sp. fungus from Taman Nasional Rawa Aopa Watumohai (TNRAW) to the successfully acclimatization and growth rate of tiger orchid planlet (Grammatophyllum scriptum Bl.) as well to know successfully infection of fungus Rhizoctonia sp. at the planlet root. The procedure of this research consists 3 main steps, they were fungus inoculation on orchid’s growing media, growth test and verification of successfully infection on planlet root. Growth test consisting of 3 treatments namely control (without nutrition and fungi) (K0); Rhizoctonia sp. application (R1); Rhizoctonia sp. + nutrition Potato Dextrose Borth (PDB) (R2) with the repetition for 8 times, then the growth data was analysed by statistics utilizes to F-test and continue by BNT-test on 95% trusty level. The result of the research showed that R2 treatment increase high planlet, leaf and root number. All the mean score of research indicator R2 was highest compared R1 and K0. The result of F-test showed R1 and R2 treatment gave significant influence toward the high planlet, leaf and root number growth. Except, fresh and dry weight planlet. Eventhough, fresh and dry weight was higher compared than K0 acclimatization period for a month.  Rhizoctonia sp. fungus infected planlet root through velamen to eksodermis and cortex by forming hifa scroll (pelotons).